Seagrass meadows support global fisheries production - Unsworth, Richard K.F.; Nordlund, Lina Mtwana; Cullen‐Unsworth, Leanne C. (Conservation letters, 2019)
The significant role seagrass meadows play in supporting fisheries productivity and food security across the globe is not adequately reflected in the decisions made by authorities with statutory responsibility for their management. We provide a unique global analysis of three data sources to present the case for why seagrass meadows need targeted policy to recognize and protect their role in supporting fisheries production and food security. (1) Seagrass meadows provide valuable nursery habitat to over 1/5th of the world's largest 25 fisheries, including Walleye Pollock, the most landed species on the planet. (2) In complex small‐scale fisheries from around the world (poorly represented in fisheries statistics), we present evidence that many of those in proximity to seagrass are supported to a large degree by these habitats. (3) We reveal how intertidal fishing activity in seagrass is a global phenomenon, often directly supporting human livelihoods. Our study demonstrates that seagrasses should be recognized and managed to maintain and maximize their role in global fisheries production. The chasm that exists between coastal habitat conservation and fisheries management needs to be filled to maximize the chances of seagrass meadows supporting fisheries, so that they can continue to support human wellbeing.